Effect of Cellulose on The Characterization of Potassium Silica – Humat Composite Gel - Suprihatin; Ika Nawang Puspitawati; Putri Sinta Dewi Sinaga; Mohamad Nabhan Putra Redian (Nusantara Science and Technology Proceedings)
Potassium-Silica Humate Composite Gel or K-Si-Humate Composite Gel is a combined material of Potassium and Silica Humate derived from the extraction of raw materials for geothermal sludge and peat soil. This material is a multipurpose material, which can be used to improve soil aeration and as a fertilizer that can fertilize the soil because it contains humic acid. The purpose of this study was to examine the effect of cellulose content on the characteristics of the Potassium Silica-Humate composite gel. The manufacture of K-Si-Humate Composite Gel in this research by extracting potassium and silica from geothermal sludge and humic acid from peat soil, then the process of filtration and gel formation. The variable used is the addition of carboxymethyl cellulose content, namely Carboxy Methyl Cellulose (CMC). The best results from this study showed that with the addition of CMC, the highest silica content was 15.85%, and the highest potassium content was 89.88%.